KORELASI PENGETAHUAN DAN MOTIVASI DENGAN KEAKTIFAN KADER POSYANDU DI WILAYAH KERJA PUSKESMAS WATES KABUPATEN PRINGSEWU LAMPUNG - Cynthia Puspariny (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2019)
The kader are community workers who are considered closer to the community and who are expected to be able to do their work voluntarily without compensation such us money and materials. around 40% of the frameworks are still less active in posyandu implementation activities. The purpose of the study are to know the correlation between knowledge and motivation with the activity of posyandu kader activities in health care centre Pringsewu Lampung district. This research uses a descriptive analysis method with a transversal approach. The instrument of this study used questionnaire. In this study, the determination of samples using the Cluster Sampling technique. The sample used was 52 respondents. The chi-square statistical test showed that there was a significant relationship between the level of knowledge and the activity of posyandu kader with P value 0,000<0,05 , and the motivation with the activity of the posyandu kader in in the health care centre 0.013 <0.05.The Efforts to increase knowledge and welfare of the frameworks must be increased to improve the role of posyandu kader activities . Keywords: knowledge, motivation and kader activities